The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.virol.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific transcription profile of cytokine and chemokine genes associated with flavivirus control and non-lethal neuropathogenesis in rabbits

Abstract: We previously showed that New Zealand White (NZWRs) and cottontail rabbits (CTRs) are a suitable model for studying immune mechanisms behind virus control and non-lethal neuropathogenesis associated with West Nile virus (WNV) and Murray Valley encephalitis virus (MVEV) infections. In the current study, we observed that MVEV infection induced high IFNα, TNFα, IL6, and CXCL10 transcript levels in the brains of weanling NZWRs, unlike infection with the less virulent WNVNSW2011. These transcript levels also correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Both of these chemokines bind to the chemokine receptor CXCR3, the signaling through which has been shown to be very important in many viral infections [54][55][56][57]. We previously demonstrated upregulation of CXCL10 in brain and draining lymph node following WNV infection in rabbits [20,21] and this was validated for the draining lymph node in this study in both dexamethasone treated and untreated rabbits. We also demonstrated equally potent upregulation of CXCL9 in a similar time-and treatment-independent manner (Figure 6B, Table 4).…”
Section: • Ifn-signalingsupporting
confidence: 71%
See 2 more Smart Citations
“…Both of these chemokines bind to the chemokine receptor CXCR3, the signaling through which has been shown to be very important in many viral infections [54][55][56][57]. We previously demonstrated upregulation of CXCL10 in brain and draining lymph node following WNV infection in rabbits [20,21] and this was validated for the draining lymph node in this study in both dexamethasone treated and untreated rabbits. We also demonstrated equally potent upregulation of CXCL9 in a similar time-and treatment-independent manner (Figure 6B, Table 4).…”
Section: • Ifn-signalingsupporting
confidence: 71%
“…In our previous studies, we demonstrated the draining popliteal lymph node was the first tissue site with detectable tissue viral load [20,21], and thus, a suitable site for study of early antiviral responses. Therefore, RNA was extracted from the draining lymph node and RNAseq was performed in order to examine potential differences in the early immune response between dexamethasone and mock-treated rabbits.…”
Section: Differential Gene Expression Analyses Of Rna Extracted From Fraining Lymph Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with severe WNV infection have downregulated IL-4, IL-1β (peripheral blood cells), and CXCL1 (myeloid dendritic cells) [ 417 , 418 ]. There is other evidence of upregulation of IFN γ, TNFα an IL-6 in the CNS during the acute phase of neuroinvasive WNV infection [ 419 ]. Likewise, it was demonstrated that IL-10 gene expression is upregulated in plasma during the acute phase of infection with WNV [ 420 ].…”
Section: Biomarkers Of Wnv Infectionmentioning
confidence: 99%
“…Firstly, a Swiss white CD1 mouse model, typically producing high mortality rate when infected with the virulent Australian strain, WNV NSW2011 , was used to explore WNV neuropathogenesis [100,219,246] (Chapter 3 and 4). The second half of this thesis established a phenotypically resistant animal model in rabbits for studying the clinical, virological, pathological and immunological features of non-lethal WNV infections with equine-virulent strains, which are the predominant presentation of human and equine WNV infections [263,311] (Chapter 5 and 6).…”
Section: Chapter 7 General Discussion and Conclusionmentioning
confidence: 99%